Microsatellite Instability and BAT-26 Marker Expression in a Mexican Prostate Cancer Population with Different Gleason Scores - Ana K. Flores-Islas; Manuel A. Rico-Méndez; Marisol Godínez-Rubí; Martha Arisbeth Villanueva-Pérez; Erick Sierra-Díaz; Ana Laura Pereira-Suárez; Saul A. Beltrán-Ontiveros; Perla Y. Gutiérrez-Arzapalo; José M. Moreno-Ortiz; Adrián Ramírez-de-Arellano (Diseases)
Background/Objectives: Prostate cancer (PCa) is one of the most common cancers in men worldwide. While standard treatments often provide good initial results, many patients eventually develop resistance and experience a more aggressive relapse. Microsatellite instability (MSI) involves variations in the lengths of microsatellite base repeats in cells. Assessing the frequency of MSI is essential, as it may identify candidates for immune checkpoint inhibitors, which have shown promising outcomes. This study focuses on evaluating the MSI frequency in Mexican PCa patients and exploring its potential relationship with tumor aggressiveness. Methods: In this study, 116 formalin-fixed paraffin-embedded tumoral tissue biopsies from Mexican patients with PCa were collected from Hospital Civil de Culiacán and Pathology and Nephropathology, Diagnosis and Research Center, in the period from 2021 to 2024. The Gleason score was assessed, and the MSI was performed by multiplex PCR with a panel of five markers (NR-27, NR-21, NR-24, BAT-25, and BAT-26). High microsatellite instability (MSI-H) was defined as two or more unstable markers, low microsatellite instability (MSI-L) as an unstable marker, and microsatellite stability (MSS) as no unstable marker. Results: We found 19.83% (23/116) MSI PCa patients, of which 21.74% (5/23) were MSI-H, and 78.26% (18/23) were MSI-L. We found a major distribution of MSI-positive cases (50% (11/22)) in Gleason score 9 patients, corresponding to prognostic group 5. In addition, we found most of the instability in the BAT-26 marker in MSI PCa patients (60.87% (14/23)). Conclusions: This study is the first to evaluate the frequency of MSI in PCa within the Mexican population. Among the Mexican patients with MSI-positive PCa, there was a predominant Gleason score 9 and a majority instability of the BAT-26 marker.